" A Comparative Study to Evaluate Changes of Free Gingiva Adjacent to Extraction Sites During Canines Retraction Using Different Levels of Orthodontic Forces (Journal of Hama University, 2022)
This study aimed to compare the effect of both 150g and 200g force systems on alteration in free gingiva dimension, during the retraction of the upper canines using closing coil springs employing and tattoo marking points that were place on the free gingiva. Split mouth design involved (30 quadrants) in 15 patients with upper dentoalveolar protrusion aged 16-25 years. the upper first premolars were extracted and after 3 weeks of extraction tattoo marking points were placed on the free gingiva, then the measurements were taken between these points using digital Vernier caliper (pied a coulisse) before starting to retract the upper canines , closed coil springs made of nickel- titanium were used to retract the upper canines and force of 150 g in one side and 200 g in the other side were applied. The force systems calibrated by the Dontix gauge, the coil springs were activated every 21 days, with measurements being retaken between points in each activation. the period to complete the retraction of the canines were took about 4-5 months. The results showed that there were no statistically significant differences in the average amount of change in the free gingiva(P>0.05) during the upper canines retraction between the two force systems (150g and 200g). there is no significant differences on alteration in free gingiva dimension during the upper canines retraction between the two force systems (150g and 200g).